Chemoselective hydrogenation of cinnamaldehyde over Pd/CeO2-ZrO2 catalysts - Bhogeswararao, Seemala; Srinivas, D. (Catalysis Letters, 2010)
Selective hydrogenation of cinnamaldehyde over Pd (2 wt%) supported on CeO2, ZrO2 and CeO2-ZrO2 catalysts is reported for the first time. In general, the olefinic (C=C) group of cinnamaldehyde is preferentially hydrogenated compared to the carbonyl (C=O) group. This selectivity preference could, however, be altered or reversed by adding alkali additives to the catalyst. The influence of additive on the structure and redox properties of the active sites and correlation of that with selective hydrogenation activity is investigated.
Keywords: alpha; beta-Unsaturated aldehyde; Ceria-zirconia; Cinnamaldehyde; Hydrogenation; palladium catalyst